Pascoia, a new Deltocephalini leafhopper genus (Hemiptera: Cicadellidae: Deltocephalinae) from Peru - Duan, Yani; Gao, Yao; Dietrich, Christopher H. (Zootaxa, 2020)
A new genus of Deltocephalini Pascoia Duan gen. n. with P. rakitovi Duan sp. n. as type species is described and illustrated from the Andes Mountains in Peru.